Draft Genome of the European Mouflon (Ovis orientalis musimon) - Su, Rui; Qiao, Xian; Gao, Yun; Li, Xiaokai; Jiang, Wei; Chen, Wei; Fan, Yixing; Zheng, Bingwu; Zhang, Yanjun; Liu, Zhihong; Wang, Ruijun; Wang, Zhiying; et al. (Frontiers in Genetics, 2020)
Mouflon (Ovis orientalis) with its huge and beautiful horns is considered as one of the ancestors of domesticated sheep. The European mouﬂon (Ovis orientalis musimon) is in the Asiatic mouflon (Ovis orientalis) clade. In order to provide novel genome information for mouflon, moreover promote genetic analysis of genus Ovis both domestic and wild, we propose to sequence the mouflon genome. We assembled the highly heterozygous mouflon genome based on Illumina HiSeq platform using the next-generation sequencing technology. Finally, the draft genome we accessed approximately 2.69 Gb (42.15% GC), while N50 sizes of contig and scaffold are 110.1 kb and 10.4 Mb, respectively. The contiguity of this assembly is obviously better than earlier versions. Further analyses predicted 20,814 protein-coding genes in the mouflon genome and 12,390 shared gene families among bovine species. It is estimated that the divergence time between Ovis orientalis musimon and Ovis aries was 7.6 million years ago. The draft mouflon genome assembly will provide data support and theoretical basis for various investigations of the genus Ovis species in future.